The Direction of Tax Policy in 2021 in the Context Increase Tax Revenue in the 19th COVID Recovery - Agus Subagiyo; Diana Prihadini; Mainita Hidayati; Dwikora Hardjo; Pebriana Arimbhi (Yayasan Ilomata, 2020)
The COVID-19 pandemic has changed economic and social developments and arrangements throughout the world. This pandemic requires the Government together with elements of the community to make efforts to prevent the spread of the virus and economic recovery. In the context of maintaining sustainable development in the midst of dynamic fundamental challenges, the National Budget as an instrument of fiscal policy is designed to be more productive, effective, and efficient in order to accelerate economic growth for welfare and improve the government's balance sheet. Global economic activity has been disrupted due to lockdown policies in a number of Indonesia's major trading partners, which has reduced supply of important components for industries from abroad. The increasing exchange rate of the US dollar makes the price of imported materials more expensive. On the consumption side, many companies experience cash flow difficulties, thereby reducing their ability to pay taxes resulting in significant tax revenues such as Corporate Income Tax. Significant reduction in international trade activities also resulted in lower tax revenues from imports and import duties. Tax revenues also experienced pressure from falling world oil prices, minerals, and CPO which are important components in calculating oil and gas PPh and export duties. Tax revenue performance is expected to weaken in 2020 with a tax ratio potentially below 9 percent. The government has made the first policy of relaxing the taxation by reducing the burden of business activities and helping to improve the condition of the company's cash flow, especially during and after the COVID-19 epidemic. The company can use a reduction in corporate income tax rates, exemption from import PPh and certain sector import duties, as well as various other tax facilities to cover increases in input material prices and decreased sales so that it continues to operate normally. Both Governments have made efforts to expand the taxation base and improve tax administration. Third The addition of new tax objects, one of which the Government levies taxes on Trade through Electronic Systems (PMSE) and other object sources of excise products such as plastics, sweetened drinks, and fuel oil (BBM). Fourth, from the aspect of tax subject by extending the taxpayers (WP), which are sector-based and regional, increase WP voluntary compliance through effective education and service improvement, including the High Net Worth Individual (HNWI) group. The Fifth Government seeks to improve tax governance and administration starting from business processes, information technology, databases (core tax), organizations, and HR. From government policies in the effort to accelerate economic recovery, there are still various obstacles, especially in terms of regulations or policies prepared as well as technology as a means of infrastructure in supporting these regulations. The regulation or policy must touch on all aspects, namely aspects of tax law, aspects of tax justice, and aspects of the Double Tax Avoidance Agreement (P3B) for cross-border transactions.